DUA SISI NIKAH BEDA AGAMA : HUKUM AGAMA VS NEGARA (PEMIKIRAN M. QURAISH SHIHAB & NURCHOLIS MADJID): Indonesia - Dina Sakinah Siregar (STAI Asy-Syukriyyah, 2023)
This research is a study that examines the concept of interfaith marriage in theory and practice in society by taking the thoughts of M. Quraish Shihab and Nurcholis Madjid as the theory of analysis and taking several court decisions as objects. This research is normative by using qualitative methods. The approach used in this normative research is a conceptual and case approach. From the results of the study, it was found that there was a prohibition on interfaith marriages both regulated in the Qur'an, KHI and MUI fatwas. However, in the law the regulation of interfaith marriage is not explicitly regulated. Researchers found several decisions of the District Court regarding the determination of interfaith marriage licenses in which the decisions refer to the rules of Law no. 23 of 2006 and relates it to the Human Rights regulated in the 1945 Constitution.